Hyperactivation of p21ras and PI3K cooperate to alter murine and human neurofibromatosis type 1–haploinsufficient osteoclast functions - Yang, Feng-Chun; Chen, Shi; Robling, Alexander G.; Yu, Xijie; Nebesio, Todd D.; Yan, Jincheng; Morgan, Trent; Li, Xiaohong; Yuan, Jin; Hock, Janet; Ingram, David A.; Clapp, D. Wade (The Journal of Clinical Investigation, 2006)
Individuals with neurofibromatosis type 1 (NF1) have a high incidence of osteoporosis and osteopenia. However, understanding of the cellular and molecular basis of these sequelae is incomplete. Osteoclasts are specialized myeloid cells that are the principal bone-resorbing cells of the skeleton. We found that Nf1+/– mice contain elevated numbers of multinucleated osteoclasts. Both osteoclasts and osteoclast progenitors from Nf1+/– mice were hyperresponsive to limiting concentrations of M-CSF and receptor activator of NF-κB ligand (RANKL) levels. M-CSF–stimulated p21ras-GTP and Akt phosphorylation was elevated in Nf1+/– osteoclasts associated with gains of function in survival, proliferation, migration, adhesion, and lytic activity. These gains of function are associated with more severe bone loss following ovariectomy as compared with that in syngeneic WT mice. Intercrossing Nf1+/– mice and mice deficient in class 1A PI3K (p85α) restored elevated PI3K activity and Nf1+/– osteoclast functions to WT levels. Furthermore, in vitro–differentiated osteoclasts from NF1 patients also displayed elevated Ras/PI3K activity and increased lytic activity analogous to those in murine Nf1+/– osteoclasts. Collectively, our results identify a what we believe to be a novel cellular and biochemical NF1-haploinsufficient phenotype in osteoclasts that has potential implications for the pathogenesis of NF1 bone disease.